Sinomenine hydrochloride injection for knee osteoarthritis: A protocol for systematic review and meta-analysis. Issue 2 (14th January 2022) - Huang, Zeling; Mao, Xiao; Chen, Junming; He, Junjun; Shi, Shanni; Gui, Miao; Gao, Hongjian; Hong, Zhenqiang
Abstract: Background: Knee osteoarthritis (KOA) is a degenerative disease in the knee joint, with chronic joint pain, swelling, stiffness, and dysfunction as the primary manifestations. Sinomenine hydrochloride injection is a proprietary Chinese medicine injection of sinomenine, the main active component of traditional Chinese medicine (TCM). Clinical studies show that Sinomenine hydrochloride injection has a good effect on the treatment of KOA. At present, there is still a lack of systematic reviews and meta-analyses to evaluate the efficacy and safety of sinomenine hydrochloride injection in the treatment of KOA. Our purpose is to supplement this deficiency. Methods: Randomized controlled trials of sinomenine hydrochloride injection in the treatment of KOA were searched for Eight electronic resource databases. We will use Review Manager 5.3 software for heterogeneity assessment, meta-analysis, and subgroup analysis. We will use the Cochrane Manual to assess the quality of the included studies, and use reporting biases assessment and sensitivity analysis to evaluate the reliability and stability of the results. Results: This study will provide a high-quality synthesis to assess the efficacy and safety of sinomenine hydrochloride injection in the treatment of KOA. Conclusion: This systematic review evaluates the efficacy and safety of sinomenine hydrochloride injection in the treatment of KOA. INPLASY registration number: INPLASY2021110057.